UNIT 1A.5 Biosafety Oversight and Compliance: What do you Mean, I have to Fill Out Another Form?!. Issue 1 (3rd November 2015) - Petrella, Brenda L.
Abstract : This unit is an overview of biosafety compliance and oversight in the United States. Specific attention is given to the oversight of the Institutional Biosafety Committee (IBC) and how the purview of the IBC may overlap with other local committees, such as the Institutional Animal Care and Use Committee (IACUC) for animal research and the Institutional Review Board (IRB) for research on human subjects. Requirements for the Federal Select Agent Program and Dual Use Research of Concern (DURC) are also briefly reviewed for those working with materials and experiments covered under these regulations. This unit serves as a guide for new and established investigators who are navigating the regulatory world and how regulatory oversight applies to their research. © 2015 by John Wiley & Sons, Inc.